Generating CAR T cells from tumor-infiltrating lymphocytes - Jane K. Mills; Melissa A. Henderson; Lauren Giuffrida; Pasquale Petrone; Jennifer A. Westwood; Phillip K. Darcy; Paul J. Neeson; Michael H. Kershaw; David E. Gyorki (SAGE Publishing, 2021)
Background: Tumor-infiltrating lymphocytes (TILs) and chimeric antigen receptor (CAR) T-cell therapies have demonstrated promising, though limited, efficacy against melanoma. Methods: We designed a model system to explore the efficacy of dual specific T cells derived from melanoma patient TILs by transduction with a Her2-specific CAR. Results: Metastatic melanoma cells in our biobank constitutively expressed Her2 antigen. CAR-TIL produced greater amounts of IFN compared with parental TIL, when co-cultured with Her2 expressing tumor lines, including autologous melanoma tumor lines, although no consistent increase in cytotoxicity by TIL was afforded by expression of a CAR. Results of an in vivo study in NSG mice demonstrated tumor shrinkage when CAR-TILs were used in an adoptive cell therapy protocol. Conclusion: Potential limitations of transduced TIL in our study included limited proliferative potential and a terminally differentiated phenotype, which would need addressing in further work before consideration of clinical translation.